2022
DOI: 10.1002/cre2.592
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of 3D‐printed, milled, and conventional oral splint resins to L929 cells and human gingival fibroblasts

Abstract: Objectives: Evidence on the biocompatibility of three-dimensional (3D)-printed and milled resins for oral splints is limited. This in vitro study assessed the influence of the manufacturing method on the cytotoxicity of oral splint resins on L929 cells and human gingival fibroblasts (GF1).Materials and Methods: Standardized specimens of four 3D-printed, two-milled, one-thermoformed, and one-pressed splint resin were incubated with L929 and GF1 cells for 24 h. Immunofluorescence and WST-8 assay were performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Wedekind et al concluded that residual monomers and additives that eluded from 3D printed materials resulted in cytotoxicity for human gingival fibroblasts and could cause allergies and cross-reactions. 27 28 Guerrero-Gironés et al 29 found that the NextDent Ortho Rigid resin had similar cellular behavior to conventional resins, supporting the use for occlusal splints, which are also used long-term. Frasheri et al 30 concluded that 3D printed materials, which included the NextDent C&B MFH resin, affected cell proliferation and induced more unfavorable effects on gingival keratinocytes.…”
Section: Discussionmentioning
confidence: 95%
“…Wedekind et al concluded that residual monomers and additives that eluded from 3D printed materials resulted in cytotoxicity for human gingival fibroblasts and could cause allergies and cross-reactions. 27 28 Guerrero-Gironés et al 29 found that the NextDent Ortho Rigid resin had similar cellular behavior to conventional resins, supporting the use for occlusal splints, which are also used long-term. Frasheri et al 30 concluded that 3D printed materials, which included the NextDent C&B MFH resin, affected cell proliferation and induced more unfavorable effects on gingival keratinocytes.…”
Section: Discussionmentioning
confidence: 95%
“…However, the MTT results showed reduced cell viability in an extract concentration-dependent manner. In a study by Bürgers et al [ 52 ], the measured cytotoxicity of the same material presented different cell viability results depending on the applied cell line, but the cell viability was not below 70%. Similarly, a slight cytotoxic effect was shown for PMMA interim material blocks [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity studies were performed on the mouse fibroblast cell line L929 and the human PC cell line DU145 . L929 is one of the cell lines to study in vitro bioreactivity and cytotoxicity of compounds, delivery systems, and medical devices proposed by the authorities for biological safety evaluation as in the ISO 10993 (Biological evaluation of medical devices) document. , …”
Section: Methodsmentioning
confidence: 99%
“…35 L929 is one of the cell lines to study in vitro bioreactivity and cytotoxicity of compounds, delivery systems, and medical devices proposed by the authorities for biological safety evaluation as in the ISO 10993 (Biological evaluation of medical devices) document. 36,37 DU145 and L929 cells were cultured in a complete medium containing Dulbecco's modified Eagle's medium (DMEM, low glucose) with 10% fetal bovine serum (FBS), 2 mM Lglutamine, and 1% penicillin−streptomycin to avoid bacterial contamination. Then, the cells were plated in 96-well plates at a density of 5 × 10 3 cells per well in 100 μL growth media and treated with increased concentrations (50,100,200,400, 600, and 800 μg/mL based on lipid concentration) of liposome formulations for 24 h. According to the manufacturer's instructions, the percentage of viable cells was assessed using the Alamar Blue Cell Viability Assay (Thermo Fisher Scientific, USA).…”
Section: Cytotoxicity Studiesmentioning
confidence: 99%